TECHNOLOGY OF WORKING WITH DICTIONARIES IN PRIMARY EDUCATION - Murodullayeva Dilsora; Khojamova Gulzoda (Western European Studies, 2024)
his article introduces the methods of working with the dictionary, which is one of the important tasks of developing speech in school, to form the technology of working on the dictionary in students, to improve the skill of working with dictionaries, to learn its main directions. it is about making, enriching the students' vocabulary and managing the growth processes.
Keywords: lexicology; dictionary; speech development; methodology